Adoption of Digital Accounting Systems among Small and Medium Enterprises in Wetland Ecosystems - Lili Safrida; Antonius Grivaldi Sondakh; Isnawati (Universitas Muhammadiyah Makassar, 2026)
Digital accounting systems represent an important component of accounting information systems that support financial recording, reporting, and decision-making in small and medium enterprises (SMEs). However, SMEs operating in environmentally constrained regions may face contextual challenges that alter the determinants of digital accounting adoption. This study examines factors influencing digital accounting system adoption among SMEs in South Kalimantan's wetland ecosystems. Drawing on the Technology Acceptance Model, Diffusion of Innovation Theory, and the Resource-Based View, this research develops an integrated framework to assess the relative influence of perceived usefulness, perceived ease of use, digital infrastructure, and digital literacy on adoption intention. Survey data were collected from 86 SME owners and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital literacy (β = 0.439, p < 0.001) is the strongest predictor of adoption intention, followed by perceived usefulness (β = 0.310, p = 0.001) and digital infrastructure (β = 0.233, p = 0.004). Perceived ease of use is not significant (β = 0.092, p = 0.435), suggesting that in chronically volatile environments baseline expectations for technological friction may be elevated, a phenomenon we term friction tolerance. Wetland ecosystem characteristics show no direct or moderating effects. The model explains 72.4% of the variance in adoption intention, indicating strong explanatory power. These findings contribute to accounting information systems literature by demonstrating that capability-based mechanisms, particularly digital literacy, assume greater explanatory weight than perceptual mechanisms in environmentally constrained settings. Practical implications emphasize prioritizing capacity-building initiatives and strategic infrastructure investment to support SME digital accounting adoption in wetland regions.